Treatments and Mortality Trends in Cases With and Without Dialysis Who Have an Acute Myocardial Infarction: An 18-Year Nationwide Experience. Issue 9 (September 2019) - Szummer, Karolina; Lindhagen, Lars; Evans, Marie; Spaak, Jonas; Koul, Sasha; Åkerblom, Axel; Carrero, Juan Jesus; Jernberg, Tomas
Abstract : Background: Patients on dialysis who have an acute myocardial infarction (AMI) have an exceedingly poor prognosis, but it is unknown to what extent guideline-recommended interventions and treatments are used and to which benefit. We aimed to assess temporal changes in the use of treatments and survival rates in dialysis patients with an AMI. Methods and Results: All consecutive AMI cases from 1996 to 2013 enrolled in the SWEDEHEART registry (Swedish Web–System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies) were included. The Swedish Renal Registry identified all chronic dialysis cases. Multivariable adjusted standardized 1-year mortality was estimated. An age-sex-calendar year–matched dialysis background population from the Swedish Renal Registry was used to obtain a standardized incidence ratio. All analyses were performed in 2-year blocks, where each individual could be included several times but in different time blocks; hence the term AMI cases and not patients is used. Of 289 699 cases with AMI, 1398 (0.5%) were on dialysis (73.6% hemodialysis; 26.4% peritoneal dialysis). Among dialysis cases, 29.4% were women, and 21.0% had ST-segment–elevation myocardial infarction. Through 1996 to 2013, dialysis cases had similar age (median, 70 years [interquartile range, 62–77]; P for trend, 0.14), but the proportion with diabetes mellitus increased (36.0%–55.3%; P for trend, 0.005). Dialysis cases admitted with AMI were treated more invasively and received more discharge medications in the later years. From 1995 to 2013, in-hospital and 1-year mortality decreased from 25.4% to 9.4% and from 59.6% to 41.2%, respectively. The standardized in-hospital and 1-year mortality decreased from 25.7% to 9.4% and from 54.6% to 41.2%. Yet, compared with the matched dialysis population, the odds of death remained as high in 2012/2013 as in 1996/1997 (odds ratio, 2.04; 95% CI, 1.62–2.58 and odds ratio, 1.99; 95% CI, 1.52–2.60, respectively; P for trend, 0.34). Conclusions: Over the last 18 years, more patients on dialysis with AMI have been treated with evidence-based therapies. Overall, dialysis cases with AMI have an improved in-hospital and 1-year survival in the more recent years compared with earlier years. However, this appears largely to be because of improved survival in the general dialysis population. Abstract : Supplemental Digital Content is available in the text.